Study on Resource Allocation in Cloud - Surendran, Swathy; Sreetha, ES; Azath, M (International Journal of Computer Sciences and Engineering, 2014)
Cloud computing is an accepted trend in current computing which provide cheap and easy access to computational resources. In cloud computing, multiple cloud users can simultaneously request cloud services. Accessing of applications and associated data from anywhere is possible using clouds. Current cloud providers do not allocate the resources efficiently. Services are delivered to large number of users as demand grows up. This survey reviews various resource allocation methods.